Analysis of erosion hazard level and land rehabilitation pattern with the RUSLE method based on GIS at Wai Tala Watershed in West Seram Regency Maluku Province - Talakua, Silwanus Matheus; Osok, Rafael M; Talakua, Cristina M (Brawijaya University, 2024)
This study used the Revised Universal Soil Loss Equation (RUSLE) and Geographical Information System (GIS) to estimate the annual rate of soil loss, map erosion factors, and recommend a suitable pattern of land rehabilitation in Wai Tala watershed, Regency of Western Seram. The research material used in this study were rainfall data for 38 years, Digital Elevation Model Nasional (DEMNAS) Image Map, Rupa Bumi Indonesia (RBI), geology, soil, land use, and watershed boundaries of Maluku Province. Field research was conducted on 187 land units, and each land unit contained RUSLE erosion factors: topography, soil type, and land use. The spatial distribution of erosion factors was processed using the Arc.GIS10.8, and the soil erosion rates were estimated using the RUSLE method, then corrected using the land degradation model developed in small islands in Maluku. The results showed that the level of erosion hazard in the Wai Tala watershed was none to slight (mean = 3.54 t/ha/yr), moderate erosion (21.52 t/ha/yr), high erosion (110.01 t/ha/yr), and very high erosion (252.84 t/ha/yr). The recommended land rehabilitation patterns that can reduce annual soil loss lower than the tolerable limit are maintaining the none to slight erosion areas with the present land uses in particular primary and secondary forests, and with reforestation or agroforestry patterns combined with low to high-density garden plants or with low to high densities cover crop at the moderate to very high erosion areas.